Religious Education for Schools Within Conflict-Prone Zones: An Inclusive Multicultural Approach - Remiswal Remiswal; Martin Kustati; Zulmuqim Zulmuqim; Mahyudin Ritonga; David D. Perrodin; Arham Junaidi Firman (Yayasan Keluarga Guru Mandiri, 2022)
The multicultural approach plays a vital role in learning religious education in order to recognize the diversity that exists, especially in conflict-prone zone schools. This study aims to describe a multicultural approach in learning religious education in conflict-prone zones. Through exercising Garfinkel’s ethnomethodology analysis, this qualitative research was conducted at SMAN 2 Pasaman and SMAN 1 Luhak Nan Duo senior high schools within conflict-prone zones of West Pasaman, West Sumatra. The dynamics of school philosophy towards inclusive multicultural approaches in religious education for schools in conflict-prone zones indicated that academic culture within said schools must be capable of creating a more harmonious atmosphere among ethnic diversities, mainly that of Javanese, Minangkabaunese, and Bataknese. The application of multicultural approaches in religious education for such schools in conflict-prone zones showed that the planning, implementation, and evaluation of religious education must be carried out while simultaneously considering the diversity of these ethnicities. The employment of an inclusive multicultural approach in association with schools in conflict-prone zones showed that the school’s physical environment is strategic for the interaction of various ethnicities, such as with Javanese, Minang, and Batak ethnicities at SMAN 2 Pasaman and SMAN 1 Luhak Nan Duo. This research is useful as input in making and improving policies by schools and the government regarding the implementation of religious education with a multicultural approach in conflict-prone zone schools.